2016
DOI: 10.1152/ajplung.00218.2015
|View full text |Cite
|
Sign up to set email alerts
|

AdipoR-increased intracellular ROS promotes cPLA2and COX-2 expressions via activation of PKC and p300 in adiponectin-stimulated human alveolar type II cells

Abstract: Adiponectin, an adipokine, accumulated in lung system via T-cadherin after allergens/ozone challenge. However, the roles of adiponectin on lung pathologies were controversial. Here we reported that adiponectin stimulated expression of inflammatory proteins, cytosolic phospholipase A2 (cPLA2), cyclooxygenase-2 (COX-2), and production of reactive oxygen species (ROS) in human alveolar type II A549 cells. AdipoR1/2 involved in adiponectin-activated NADPH oxidase and mitochondria, which further promoted intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…For example, lung epithelial cells of cystic fibrosis (CF) patients have elevated cPLA 2 activity and produce more eicosanoids than do normal epithelial cells (73). Activation of cPLA 2 via phosphorylation is imperative for the production of eicosanoids and is dependent on MAP kinases and protein kinase C (PKC) (42,50,74), and we found that phosphorylated cPLA 2 accumulated in the membrane fraction of lung epithelial cells after pneumococcal infection.…”
Section: Discussionmentioning
confidence: 82%
“…For example, lung epithelial cells of cystic fibrosis (CF) patients have elevated cPLA 2 activity and produce more eicosanoids than do normal epithelial cells (73). Activation of cPLA 2 via phosphorylation is imperative for the production of eicosanoids and is dependent on MAP kinases and protein kinase C (PKC) (42,50,74), and we found that phosphorylated cPLA 2 accumulated in the membrane fraction of lung epithelial cells after pneumococcal infection.…”
Section: Discussionmentioning
confidence: 82%
“…In studies with A549 cells, AdipoR1 (but not AdipoR2) was strongly expressed after stimulation with TNF-a (as assessed with RT-PCR, immunohistochemistry, and Western Blot), whereas unstimulated A549 cells did not express AdipoR1 (Miller et al, 2009). In two different studies, the two subtypes of AdipoRs were found to be expressed at the mRNA and protein levels in A549 cells and in two other human lung cell lines (SW-1573 and Calu-3) (Chen et al, 2016;Cheng et al, 2016). However, an immunohistochemistry study of lung sections from patients with COPD demonstrated that airway epithelial cells expressed significant levels of AdipoR1 but not of AdipoR2 (Miller et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…However, in Nigro et al's study (Nigro et al, 2013) of the same cell line, incubation with full-length APN (5 or 50 µg.ml -1 for 14 h) did not influence the mRNA expression of CXCL-8, CCL-2, and IL-6. Furthermore, Chen et al reported that full-length APN upregulated cytosolic phospholipase A2 and cyclooxygenase-2 in the A549 cell line (Chen et al, 2016). The A549 cell line is a hypotriploid human cell line initiated by the explant culture of lung carcinomatous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, the phenotypes of adiponectin-deficient mice have not been thoroughly replicated by the AdipoR1/R2 dual-deficient mice [116]. Moreover, a number of studies have suggested a pro-inflammatory role of AdipoR1/R2 [135,136]. AdipoR1 and AdipoR2, as well as other members of the progestin and AdipoQ receptor superfamily, possess potent ceramidase activities to produce ceramide and phosphorylated sphingoid, which are causatively involved in the development of insulin resistance, atherosclerosis and heart failure [137 -140].…”
Section: Receptors and Signaling Pathways Of Adiponectinmentioning
confidence: 99%